Air conditioning versus heating: climate control is more energy demanding in Minneapolis than in Miami - Michael Sivak (Environmental Research Letters, 2013)
Energy demand for climate control was analyzed for Miami (the warmest large metropolitan area in the US) and Minneapolis (the coldest large metropolitan area). The following relevant parameters were included in the analysis: (1) climatological deviations from the desired indoor temperature as expressed in heating and cooling degree days, (2) efficiencies of heating and cooling appliances, and (3) efficiencies of power-generating plants. The results indicate that climate control in Minneapolis is about 3.5 times as energy demanding as in Miami. This finding suggests that, in the US, living in cold climates is more energy demanding than living in hot climates.